Synthesis and Characterization of Hydroxyapatite Powders From Eggshell For Functional Biomedical Application - Bulus, Erdi; Ismik, Deniz; Mansuroglu, Demet Sezgin; Sahin, Yesim Muge; Tosun, Gul (Ieee, 2017)
Apatitic phosphates are considered within the category of bioceramics. HA and its derives are used of in the fields of medicine, orthopedics and dentistry in order to support a grow up of new bone cells. HA structures have a high biocompability and are widely in biomedical applications. On the other hand, synthesis of HA structures necessitates complex technologies (microwave sintering, hydrothermal synthesis etc.) and their production costs high. This study aims the production of nano apatitic structures with great biocompability from a natural material. Simple hotplate method was used to obtain natural, nano scale HA from eggshells. After calcination and sintering processes at different temperatures, the obtained apatitic phosphate powders have been structurally characterized by infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). Morphological investigation has been conducted by FEG-SEM images. Biological investigations have been carried out for the produced nanosized bioceramics and the results reveal that these nanomaterials are promising for tissue engineering purposes.
Scientific Meeting on Electric Electronics, Computer Science, Biomedical Engineerings (EBBT) -- APR 20-21, 2017 -- Istanbul Arel Univ, Istanbul, TURKEY
Keywords: Apatitic phosphates; nanobioceramics; biocompatible; hydroxyapatite; hotplate method; biological investigation